Zwierzęce szczątki kostne z dawnego grodu w Dusinie, stanowisko 1, gm. Gostyń - Makowiecki, Daniel (Folia Praehistorica Posnaniensia, 2021)
This article presents the results of a specialist archaeozoological analysis of materials from an early medieval stronghold in Dusina, in southern Greater Poland. The examined bones come from millennium excavations and are a fragment of the collection obtained at that time. The remains were subjected to a description of zoological, anatomical and biological features, presenting the composition of individual taxa, as well as identifying traces on bones, indicating slaughtering activities and preferences in the selection of animal carcass parts